Nickel‐Mediated Enantioselective Photoredox Allylation of Aldehydes with Visible Light. Issue 11 (24th January 2022) - Calogero, Francesco; Potenti, Simone; Bassan, Elena; Fermi, Andrea; Gualandi, Andrea; Monaldi, Jacopo; Dereli, Busra; Maity, Bholanath; Cavallo, Luigi; Ceroni, Paola; Cozzi, Pier Giorgio
Abstract: Here we report a practical, highly enantioselective photoredox allylation of aldehydes mediated by chiral nickel complexes with commercially available allyl acetate as the allylating agent. The methodology allows the clean stereoselective allylation of aldehydes in good to excellent yields and up to 93 % e.e. using a catalytic amount of NiCl2 (glyme) in the presence of the chiral aminoindanol‐derived bis(oxazoline) as the chiral ligand. The photoredox system is constituted by the organic dye 3DPAFIPN and a Hantzsch's ester as the sacrificial reductant. The reaction proceeds under visible‐light irradiation (blue LEDs, 456 nm) at 8–12 °C. Compared to other published procedures, no metal reductants (such as Zn or Mn), additives (e.g. CuI) or air‐sensitive Ni(COD)2 are necessary for this reaction. Accurate DFT calculations and photophysical experiments have clarified the mechanistic picture of this stereoselective allylation reaction. Abstract : A practical stereoselective photoredox nickel‐mediated allylation of aliphatic and aromatic aldehydes is reported (89–94 % e.e.). The reaction proceeds under visible‐light irradiation using the available organic dye 3DPAFIPN as photocatalyst in combination with a chiral IndaBOX nickel complex and Hantzsch's ester; that is, replacing stoichiometric metal reductants such as Zn and Mn.